Changes in plasma electrolytes and gill histopathology in wild Liza saliens from the Esmoriz-Paramos coastal lagoon, Portugal - Fernandes, Conceição (2011)
The Esmoriz-Paramos is a lagoon of great ecological significance located on the Northwest coast of Portugal. The quality of water and sediment within this ecosystem has been gradually degraded due to the discharges of mostly untreated industrial waste and domestic sewage. Contaminants include heavy metals that can be taken up by fish from water, food, sediments, and suspended particulate material. Fish inhabiting polluted water bodies tend to accumulate many chemicals in high concentrations, even when the environmental contamination levels are low (Colombo et al. 1995). The leaping grey mullet (Liza saliens) is one of a few dominant species living in this environment. This species may contact xenobiotics in the water column or, when feeding, in the sediments.